Lipid labeling from acetate or glycerol in cultured embryos of Camelina sativa seeds: A tale of two substrates. (October 2015) - Pollard, Mike; Delamarter, Danielle; Martin, Tina M.; Shachar-Hill, Yair
Graphical abstract: Use of acetate and glycerol substrates for prolonged 13 C-labeling of lipids by cultured developing embryos of Camelina sativa was validated and quantified. Acyl fluxes at biosynthetic branch points were correlated with total flux. Glycerol-3-phosphate synthesis does not control triacylglycerol accumulation. Highlights: Lipid synthesis by cultured developing embryos from Camelina sativa was quantified. Acetate incorporation saturates at 5% of endogenous fatty acid synthesis. At saturation, glycerol labeling essentially replaces endogenous contribution. Competition between elongation and 12-desaturation for oleate is independent of flux. Competition between 12- and 15-desaturation for linoleate is dependent on flux. Abstract: Studies on the metabolism of lipids in seeds frequently use radiolabeled acetate and glycerol supplied to excised developing seeds to track the biosynthesis of acyl and lipid head groups, respectively. Such experiments are generally restricted to shorter time periods and the results may not quantitatively reflect in planta rates. These limitations can be removed by using cultured embryos, provided they mimic growth and lipid deposition observed for embryos in planta . Mid-maturation embryos from Camelina sativa were cultured in vitro to assess the use of sufficient acetate or glycerol concentrations and labeling periods for stable isotope labeling and mass spectrometric detection. Maximum incorporation of exogenous acetate into fatty acids occurred at 1 mM and above. This provides about 5% of the total carbon flux entering fatty acids, enough for 13 C isotopomer analysis while maintaining normal biosynthetic rates for over 24 h. Labeling analysis indicates that acetate reports lipid metabolism uniformly across the embryo. At higher acetate concentrations with longer incubations, the rate of fatty acid synthesis is reduced and the composition of newly synthesized fatty acids changes. While the mole fractions of oleate that undergo Δ12-desaturation or elongation are independent of biosynthetic flux, Δ15-desaturation shows a bimodal dependence. These observations are consistent with changes occurring in planta over seed development. Incorporation rates of the glyceryl moiety into lipids saturates at about 0.5 mM exogenous glycerol. At saturation, the exogenous glycerol almost completely replaces the endogenous supply of glycerol-3-phosphate without affecting net lipid accumulation or fatty acid composition. It is concluded that acetate and glycerol labeling of cultured C. sativa embryos can provide an accurate representation of lipid metabolism in embryos in vivo, and that in Camelina embryos glycerol-3-phosphate levels do not co-limit triacylglycerol synthesis.